Green Energy Sources Assessment Using Sentinel-1 Satellite Remote Sensing - Majidi Nezhad, Meysam; Nastasi, Benedetto; Groppi, Daniele; Lamagna, Mario; Piras, Giuseppe; Astiaso Garcia, Davide (Frontiers in Energy Research, 2021)
Due to the growing use of Renewable Energy Sources (RES), the activities of mapping, monitoring, measurement and detection of various RES became crucial. This importance is even greater when researchers face a shortage of measuring instruments and tools in many parts of the world. Assessing and measuring RES are very complex since different environmental conditions occur. RES assessment is a challenging task that requires accurate and continuous measurement methods. Currently, traditional methods are very time consuming and require spending money and human sources. So, the use of accurate and fast tools for measuring RES are seriously recommended, which can greatly help the growth of the use of these sources. Satellites remote sensing technologies and techniques for RES assessing are fast, accurate and can help to reduce costs and risks in decision making of projects and to provide suitable products to the end-user. Actually, in order to use and develop it as much as possible, a correct interdisciplinary understanding is needed. In this paper, a comprehensive review on wind, wave, biomass, geothermal resources assessment using Sentinel-1 (S-1) Synthetic Aperture Radar (SAR) satellite estimation has been summarized along with the different techniques available to measure them using satellites. In the paper, few of the successful estimation techniques were introduced in each section and compared for the understanding of these different methods of RES availability evaluation.